Temperature regimes of formation of nanometer periodic structure of adsorbed atoms in GaAs semiconductors under the action of laser irradiation - Peleshchak, R.M.; Kuzyk, O.V.; Dan'kiv, O.O. (Condensed Matter Physics, 2015)
The theory of nucleation of nanoscale structures of the adsorbed atoms (adatoms), which occurs as a result of the self-consistent interaction of adatoms with the surface acoustic wave and electronic subsystem is developed. Temperature regimes of formation of nanoclusters on n-GaAs surface under the action of laser irradiation are investigated. The offered model permits to choose optimal technological parameters (temperature, doping degree, intensity of laser irradiation) for the formation of the surface periodic defect-deformation structures under the action of laser irradiation. Розвинуто теорiю нуклеацiї нанорозмiрних структур адсорбованих атомiв (адатомiв), яка вiдбувається в
результатi самоузгодженої взаємодiї адатомiв з поверхневою акустичною хвилею та електронною пiдсистемою. Дослiджено температурнi режими формування нанокластерiв на поверхнi n-GaAs пiд дiєю
лазерного опромiнення. Запропонована модель дозволяє вибрати оптимальнi технологiчнi параметри
(температуру, ступiнь легування, iнтенсивнiсть лазерного опромiнення) для формування поверхневих
перiодичних дефектно-деформацiйних структур пiд дiєю лазерного опромiнення.